PENGARUH TATA KELOLA PERUSAHAAN, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019) - Maulana Hafizh Dimasyqi; Faisal Faisal (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of corporate governance, profitability, and firm size on firm value where the variables used in this study are the dependent variable (firm value) and the independent variable (corporate governance consisting of managerial ownership, institutional ownership, and board). independent commissioners, as well as profitability and company size).The population in this study are all sectors listed on the Indonesia Stock Exchange for the 2017-2019 period. The sample was taken by using purposive sampling method. Based on the purposive sampling method, the samples obtained were 103 companies for three consecutive years (2017-2019). The analytical method used in this research is multiple linear regression analysis.The results in this study indicate that managerial ownership, independent board of commissioners, profitability, and firm size have a positive effect on firm value, while institutional ownership has a negative effect on firm value.